Isolation and Purification of Single Gold Nanoclusters by Alternate Pumping Chromatography - Supper, Malvina; Birner, Virginia; Gromotka, Lukas; Peukert, Wolfgang; Kaspereit, Malte (Separations, 2023)
Alternate pumping chromatography is applied to obtain atomically precise glutathione-stabilized gold nanoclusters in high purity from synthesized mixtures. On the basis of anion exchange chromatography, the feasibility of isolating a single cluster, Au10 GSH10, as well as two different clusters simultaneously (Au25 GSH18 and Au29 GSH20) is demonstrated. In addition, Au18 GSH14, which is present only in trace amounts, is successfully enriched. A simple design procedure is proposed that allows using columns with different retention behavior. Successful experiments with large injection amounts confirm the potential of the concept for preparative-scale productions of high-quality nanoparticulate product